Role of Proangiogenic Factors in Immunopathogenesis of Multiple Sclerosis - Kabir Magaji Hamid; Abbas Mirshafiey (Iranian Journal of Allergy, Asthma and Immunology, 2016)
Angiogenesis is a complex and balanced process in which new blood vessels form from preexisting ones by sprouting, splitting, growth and remodeling. This phenomenon plays a vital role in many physiological and pathological processes. However, the disturbance in physiological process can play a role in pathogenesis of some chronic inflammatory diseases, including multiple sclerosis (MS) in human and its animal model. Although the relation between abnormal blood vessels and MS lesions was established in previous studies, but the role of pathological angiogenesis remains unclear. In this study, the link between proangiogenic factors and multiple sclerosis pathogenesis was examined by conducting a systemic review. Thus we searched the English medical literature via PubMed, ISI web of knowledge, Medline and virtual health library (VHL) databases. In this review, we describe direct and indirect roles of some proangiogenic factors in MS pathogenesis and report the association of these factors with pathological and inflammatory angiogenesis.